The Prevalence of Pediculosis Capitis at Orphanages in Palembang City, South Sumatera (Indonesia) - Jhon Riswanda; Chairil Anwar; Mohammad Zulkarnain; Rico Januar Sitorus; Ahmad Ghiffari (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Pediculosis capitis is an endemic parasitosis affecting many countries of the world. A total of 5318 elementary schoolchildren, aged 8 -16 years, were examined for the presence of Pediculus capitis. The aim of this study was to investigate the incidence of head lice infestation in Palembang City. This research is a quantitative research with cross sectional research design. This research was conducted at the Palembang City Orphanage.. This research took place from July to September 2021. The research population was taken from orphanage children in 16 orphanages from 12 sub-districts in the city of Palembang as many as 3.823 peoples. The sample of this research is 300 people. The sampling technique in this study was by random sampling. Data collection using a questionnaire. Data analysis with chi-square test. The results of the research are the Prevalence of Pediculosis Capitis at Orphanages in Palembang City, South Sumatera (Indonesia) from 300 peoples found that the prevalence rate in urban areas (n=155) the highest number of sufferers was found in the Sako sub-district with 18 people (11.6%) and in rural areas (n=145) the number of sufferers was found in 2 research locations, namely in Indralaya 1 as many as 36 people (24.8%) and East Baturaja as many as 40 people (27.6%). Factors associated with Pediculosis Capitis at Orphanages in Palembang City, South Sumatra (Indonesia), namely such as children's health care (p-value=0.046), use of tools together p-value=0.004), children living with parents (p-value= ≤ 0.001), past infestation of fleas (p-value=0.027), lighting conditions of residential space (p-value=0.005) , teacher health education in schools (p-value=0.007), using general items (p-value=≤ 0.001), room conditions per student (p-value=0.028), and number of hairbrushes per day (p-value=0.016). Based on these results, it is suggested to the orphanage to provide socialization or health education as a preventive measure for Pediculosis capitis in order to increase knowledge and quality of personal hygiene in the orphanage by changing the attitude of each individual, especially children. Keywords: Pediculosis capitis, Hair lice infestation